Prophylactic and therapeutic protection of human IgG purified from sera containing anti-exotoxin A titers against pneumonia caused by Pseudomonas aeruginosa - Jin Zhang; Chuang Wan; Bo Yu; Chen Gao; Liqun Zhao; Xin Cheng; Feng Yang; Hao Gu; Quanming Zou; Jiang Gu; Xingyong Wang (Taylor & Francis Group, 2019)
Antibodies are effective alternative tools to combat infections caused by Pseudomonas aeruginosa (PA), especially multi-drug-resistant PA. Thus, to solve the urgent need for an anti-PA antibody drug, we hypothesized that anti-PA intravenous immunoglobulins could be a practical attempt. Exotoxin A (ETA) is one of the most important factors for PA infection and is also a critical target for the development of immune interventions. In this study, a total of 320 sera were collected from healthy volunteers. The concentration of ETA-specific antibodies was determined by a Luminex-based assay and then purified by affinity chromatography. The purified IgGs were able to neutralize the cytotoxicity of ETA in vitro. We showed they had a prophylactic and therapeutic protective effect in PA pneumonia and ETA toxemia models. In addition, administration of nonspecific IgGs also provided partial protection. Collectively, our results provide additional evidence for IVIG-based treatment of infections caused by multi-drug-resistant PA and suggest that patients at high risk of PA pneumonia could be prophylactically treated with anti-ETA IgGs or even with nonspecific IgGs.